Vascular Endothelin Receptor Type B: Structure, Function and Dysregulation in Vascular Disease - Mazzuca, Marc Q. (2012)
Endothelin-1 (ET-1) is a major regulator of vascular function, acting via both endothelin receptor type A (ET(A)R) and type B (ET(B)R). Although the role of ET(A)R in vascular smooth muscle (VSM) contraction has been studied, little is known about ET(B)R. ET(B)R is a G-protein coupled receptor with a molecular mass of ~50 kDa and 442 amino acids arranged in seven transmembrane domains. Alternative splice variants of ET(B)R and heterodimerization and cross-talk with ET(A)R may affect the receptor function. ET(B)R has been identified in numerous blood vessels with substantial effects in the systemic, renal, pulmonary, coronary and cerebral circulation. ET(B)R in the endothelium mediates the release of relaxing factors such as nitric oxide, prostacyclin and endothelium-derived hyperpolarizing factor, and could also play a role in ET-1 clearance. ET(B)R in VSM mediates increases in [Ca(2+)](i), protein kinase C, mitogen-activated protein kinase and other pathways of VSM contraction and cell growth. ET-1/ET(A)R signaling has been associated with salt-sensitive hypertension (HTN) and pulmonary arterial hypertension (PAH), and ET(A)R antagonists have shown some benefits in these conditions. In search for other pathogenetic factors and more effective approaches, the role of alterations in endothelial ET(B)R and VSM ET(B)R in vascular dysfunction, and the potential benefits of modulators of ET(B)R in treatment of HTN and PAH are being examined. Combined ET(A)R/ET(B)R antagonists could be more efficacious in the management of conditions involving upregulation of ET(A)R and ET(B)R in VSM. Combined ET(A)R antagonist with ET(B)R agonist may need to be evaluated in conditions associated with decreased endothelial ET(B)R expression/activity.